2012
DOI: 10.1007/s11789-012-0044-8
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen/LDL apheresis is a promising rescue therapy for sudden sensorineural hearing loss

Abstract: BackgroundFibrinogen/LDL apheresis has been proven to be effective in treatment of sudden sensorineural hearing loss (SSNH). This study is aimed to investigate if reduction of fibrinogen and serum LDL is also effective in patients with SSNH non-responding toward treatment with corticosteroids and plasmaexpanders.MethodsRemission rates of 217 patients suffering from SSHL were investigated after treatment with apheresis. All patients were non-responders after other therapies such as high doses of steroids or pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 19 publications
1
14
0
3
Order By: Relevance
“…If there were additional findings suggestive of saccular or otolith dysfunction, it is better treated with thrombolytics or rtPA. (12) ORIGINAL ARTICLE In our study, there were no adverse reactions or long term side effects by rtPA therapy. The advantage of rtPA even in a failed trans tympanic steroid therapy is well documented in our study CONCLUSION: Sudden Sensorineural hearing loss (SSHNL or ISSHNL) is a challenging problem in ENT practice.…”
Section: Outcome Measuresupporting
confidence: 48%
“…If there were additional findings suggestive of saccular or otolith dysfunction, it is better treated with thrombolytics or rtPA. (12) ORIGINAL ARTICLE In our study, there were no adverse reactions or long term side effects by rtPA therapy. The advantage of rtPA even in a failed trans tympanic steroid therapy is well documented in our study CONCLUSION: Sudden Sensorineural hearing loss (SSHNL or ISSHNL) is a challenging problem in ENT practice.…”
Section: Outcome Measuresupporting
confidence: 48%
“…Other works instead, on the basis of fibrinogen rheological properties, highlighted the association between high fibrinogen levels and reduced blood flow in the inner ear with major risk of SSNHL onset (Suckfull et al, 2002;Canis et al, 2012;Bao et al 2015). Quaranta et al (2015) did not find any significant difference in terms of fibrinogen level between patients with and without hearing improvement (p ¼ 0.22).…”
Section: Discussionmentioning
confidence: 99%
“…reported that HMG‐CoA reductase inhibitors may have a role in the treatment of ISSNHL with potential benefits at the cochlear level. In addition, fibrinogen and LDL apheresis have been used as a rescue therapy in some medical centres for treatment of sudden sensorineural hearing loss …”
Section: Discussionmentioning
confidence: 99%
“…In addition, fibrinogen and LDL apheresis have been used as a rescue therapy in some medical centres for treatment of sudden sensorineural hearing loss. 25…”
Section: Synopsis Of Key Findingsmentioning
confidence: 99%